Hobbes against hate speech - Bejan, T (Taylor and Francis, 2022)
This article argues that Thomas Hobbes' analysis of insult or ‘contumely’ prefigures recent developments in moral and political philosophy in striking ways. Specifically, Hobbes's concerns about the dignitary harms in hate speech went well beyond ‘fighting words’ to the essential role played by expressions of hatred and contempt in making and unmaking social hierarchies. Hobbes’s sensitivity to contumely’s subtle power to constitute social in/equalities recalls recent work in feminist and critical race theory. Yet his expansive solutions – both negative and positive, legal and ethical – also shed light on the difficulties faced by aspirationally egalitarian societies in their efforts to eradicate contempt today.